Degradation of phenylethanoid glycosides in Osmanthus fragrans Lour. flowers and its effect on anti-hypoxia activity - Fei Zhou (Nature Portfolio, 2017)
Abstract This study was aimed at investigating the chemical stability (the thermal, light and pH stability) of phenylethanoid glycosides (PhGs) in Osmanthus fragrans Lour. flowers, identifying the degradation products of acteoside and salidroside (major PhGs in O. fragrans flowers) by UPLC–QTOF–MS and studying the anti-hypoxia activity of PhGs after degradation. The degradation of PhGs followed first-order reaction kinetics, and the rate constant of acteoside (4.3 to 203.4 × 10−3 day−1) was higher than that of salidroside (3.9 to 33.3 × 10−3 day−1) in O. fragrans flowers. Salidroside was mainly hydrolyzed to tyrosol during storage, and the degradation products of acteoside were verbasoside, caffeic acid, isoacteoside, etc. In a model of cobalt chloride (CoCl2)-induced hypoxia in PC12 cells, the anti-hypoxia ability of PhGs decreased after degradation, which resulted from the reduction of PhGs contents. Particularly, caffeic acid exhibited stronger anti-hypoxia ability than acteoside and could slightly increase the anti-hypoxia ability of degraded acteoside. The results revealed that high temperature, high pH and light exposure caused PhGs degradation, and thus the anti-hypoxia ability of PhGs reduced.